Analysis of Vitamin C (ascorbic acid) in Cucumis mel L. var reticulatus Naudin and Averrhoa bilimbi L. Fruit using UV-Vis Spectrophotometry - Syahputra, Hafid; Muhammad Rivai; Shafira Mahrani; Yasmeen Nazhifah (Indonesian Journal of Pharmaceutical and Clinical Research, 2023)
Cucumis mel L. var reticulatus Naudin and Averrhoa bilimbi L. are known to possess significant chemicals that offer health benefits, including the presence of vitamin C. Vitamin C, classified as a water-soluble vitamin, possesses the potential to exert a significant influence in the prevention of several diseases. The objective of this experiment was to analyze the concentrations of vitamin C present in Cucumis mel L. var reticulatus Naudin and Averrhoa bilimbi L. using the UV-Vis spectrophotometry method. The test was performed qualitatively with FeCl3 reagen and quantitatively with 2,6-dichlorophenol indophenol using UV-Vis spectrophotometry. The results showed that the levels of vitamin C in Cucumis mel and Averrhoa bilimbi fruit were 44.523 mg/100g and 48.666 mg/100 g, respectively.